UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN DADAP SEREP (ERYTHRINA LITHOSPERMA MIQ) TERHADAP PERTUMBUHAN BAKTERI SALMONELLA TYPHII ATCC 13313 - putri wardani, Erlin; Sipriyadi; mulia, Putri; Slamet, Samwilson; danang kurniawan, Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The bacterium Salmonella typhii ATCC 13313 causes typhoid fever, which remains a medical problem in Indonesia. To prevent bacterial resistance, the misuse of antibiotics may lead to the use of alternative antibacterial agents derived from natural sources. The dadap serep leaf, or Erythrina lithosperma Miq, is a plant with potential as an antibacterial agent because it contains secondary metabolites such as alkaloids, flavonoids, triterpenoids, and phenols. The objective of this study was to determine the antibacterial properties of a 96% ethanol extract from dadap serep leaves that affect the growth of Salmonella typhii ATCC 13313. The disk diffusion method was used in this study. The maceration method with 96% ethanol was used to prepare the dadap serep leaf extract. Concentrations of 20%, 40%, 60%, 80%, and 100% were tested. Chloramphenicol was used as a positive control, and DMSO was used as a negative control. After 24-hour incubation at 37°C, inhibition zones around the disk paper indicated antibacterial activity. The results of the study show that the ethanol extract of Erythrina lithosperma Miq. leaves has a yield of 13.86% and is capable of inhibiting the growth of Salmonella typhii ATCC 13313. The higher the concentration of the extract, the greater the inhibitory effect it produces. Therefore, the ethanol extract of Erythrina lithosperma Miq. leaves may serve as a natural antibacterial agent against Salmonella typhii ATCC 13313.